Impact of Dietary Input of Rice Based Concentrate Rations on In Vitro Rumen Fermentation Characteristics in Goats - Nanthini, Ruba; C.Valli; L.Radhakrishnan; D.Balasubramanyam; A. Mangalagowri (Indian Journal of Animal Nutrition, 2023)
In Tamil Nadu, a southern state of India, it is a common practice to feed rice abundantly to goats reared especially in urban and semiurban areas. Hence, a study was conducted to document the in vitro rumen fermentation characteristics in goats, in rations with high levels of rice based concentrate. The study tested four roughage to concentrate ratios viz., 45: 55, 40: 60, 35: 65 and 30: 70 through in vitro gas production technique in six runs, using goat rumen liquor at different incubation hours (9, 12, 18 and 24). The concentrate component of the ration comprised of a blend of broken rice (70%) and de-oiled rice bran (30%). Significantly (P < 0.05) lowest in vitro ruminal pH for all incubation hours was observed in roughage to concentrate ratio of 30:70 and significantly (P < 0.05) highest in vitro ruminal pH for all incubation hours was observed in roughage to concentrate ratio of 45:55. Increasing the concentrate caused linear increase in the in vitro gas production, in vitro apparent dry matter degradability and total volatile fatty acids for all incubation hours in a significant (P < 0.05) manner. The percentage of acetate and propionate production significantly (P < 0.05) declined and increased respectively with increase in concentrate. Significantly (P < 0.05) highest energetic efficiency was observed in 30:70 roughage to concentrate ratio at all incubation hours.